The association of AGTR2 polymorphisms with preeclampsia and uterine artery bilateral notching is modulated by maternal BMI - Zhou, A.; Dekker, G.A.; Lumbers, E.R.; Lee, S.Y.; Thompson, S.D.; McCowan, L.M.E.; Roberts, C.T. (Placenta (Eastbourne), 2013)
This study aimed to determine the association of AGTR1 and AGTR2 polymorphisms with preeclampsia and whether these are affected by environmental factors and fetal sex. Overall 3234 healthy nulliparous women, their partners and babies were recruited prospectively to the SCOPE study in Adelaide and Auckland. Data analyses were confined to 2121 Caucasian parent-infant trios, among whom 123 had preeclamptic pregnancies. 1185 uncomplicated pregnancies served as controls. DNA was extracted from buffy coats and genotyped by utilizing the Sequenom MassARRAY system. Doppler sonography on the uterine arteries was performed at 20 weeks' gestation. Four polymorphisms in AGTR1 and AGTR2 genes, including AGTR1 A1166C, AGTR2 C4599A, AGTR2 A1675G and AGTR2 T1134C, were selected and significant associations were predominately observed for AGTR2 C4599A. When the cohort was stratified by maternal BMI, in women with BMI ≥ 25 kg/m2, the AGTR2 C4599A AA genotype in mothers and neonates was associated with an increased risk for preeclampsia compared with the CC genotype [adjusted OR 2.1 (95% CI 1.0–4.2) and adjusted OR 3.0 (95% CI 1.4–6.4), respectively]. In the same subset of women, paternal AGTR2 C4599A A allele was associated with an increased risk for preeclampsia and uterine artery bilateral notching at 20 weeks' gestation compared with the C allele [adjusted OR 1.9 (95% CI 1.1–3.3) and adjusted OR 2.1 (95% CI 1.3–3.4), respectively]. AGTR2 C4599A in mothers, fathers and babies was associated with preeclampsia and this association was only apparent in pregnancies in which the women had a BMI ≥ 25 kg/m2, suggesting a gene–environment interaction.